Efektivitas Assesment Berbasis Kelas Dan Kompetensi Guru Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri Di Gugus 8 Kabupaten Bandung - Abduloh Abduloh; Saepul Ma'mun (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
Student learning outcomes are tangible skills that can be measured in the form of knowledge, skills and attitudes as active interactions between subjects and learning objects during the learning process to achieve learning outcomes. One important factor is how much effectiveness the implementation of classroom-based assessment and teacher competence in improving student learning outcomes. This research was conducted with a quantitative approach and survey methods using questionnaires and interviews. The population is 135 people, a sample of 60 people in the Bandung Regency Cluster 8 Middle School teachers fill out a questionnaire. There is a significant influence of variable (X1) on variable (Y) of r = 0.784, and r2 = 0.614. Shows that the variable (X1) determinant factors to the variable (Y) gives a positive influence so that changes in the variable (Y), influenced by other factors. There is a significant influence of variable (X2) on variable (Y) r = 0.493, and r2 = 0.243. This shows that the variable (X2) determinant factors to the variable (Y) gives a positive effect so that changes in the variable (Y) are influenced by other factors. There is a significant influence between variable (X1) and variable (X2) with variable (Y) r = 0.787, and r2 = 0.620, regression equation: Y = 41.164 + 0.427 X2. Containing a significant understanding is to be expected, if an increase in variable (X1) and variable (X2) is one point, there will be a change in variable (Y) of 0.427 points. To achieve quality schools, the improvement in student learning outcomes is positively influenced by two determinant factors together, the effectiveness of classroom-based assessments and teacher competency where the improvement in student learning outcomes is subjected to the creation of quality schools. Based on the conclusions and it is recommended that the effectiveness of classroom-based assessments and teacher competencies should be further improved in the ability (ability) to manage the class, so that student learning outcomes will increase and quality in accordance with the objectives of national education. Keyworks: effectiveness of classroom-based assessments, teacher competencies, learning outcomes